2005
DOI: 10.1029/2005wr004023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of capillarity on a simple harmonic oscillating water table: Sand column experiments and modeling

Abstract: [1] Comprehensive measurements of the water table response to simple harmonic forcing at the base of a sand column are presented and discussed. In similar experiments, Nielsen and Perrochet (2000) observed that fluctuations in the total moisture were both damped and lagged relative to the water table fluctuations. As a result, the concept of a complex effective porosity was proposed as a convenient means to account for the damping and phase lag through its magnitude and argument, respectively. The complex effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
81
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(89 citation statements)
references
References 23 publications
8
81
0
Order By: Relevance
“…Using this equation, various numerical and analytical studies have been conducted to investigate the groundwater table fluctuations affected by various geometric and oceanic forcing factors, e.g., sloping beach (Nielsen, 1990) and spring-neap tides (Li et al, 2000c). However, these studies neglected the effect of vadose zone, which is expected to alter the water movement in the saturated zone and thus groundwater table fluctuations (Cardenas, 2010;Cartwright et al, 2005;Moench, 2008). Situated above the phreatic surface (water table), the vadose zone includes a capillary fringe (fully saturated zone with pressure less than the atmospheric pressure) and unsaturated zone (partly saturated zone with pressure also less than the atmospheric pressure).…”
Section: Introductionmentioning
confidence: 99%
“…Using this equation, various numerical and analytical studies have been conducted to investigate the groundwater table fluctuations affected by various geometric and oceanic forcing factors, e.g., sloping beach (Nielsen, 1990) and spring-neap tides (Li et al, 2000c). However, these studies neglected the effect of vadose zone, which is expected to alter the water movement in the saturated zone and thus groundwater table fluctuations (Cardenas, 2010;Cartwright et al, 2005;Moench, 2008). Situated above the phreatic surface (water table), the vadose zone includes a capillary fringe (fully saturated zone with pressure less than the atmospheric pressure) and unsaturated zone (partly saturated zone with pressure also less than the atmospheric pressure).…”
Section: Introductionmentioning
confidence: 99%
“…Childs and Poulovassilis, 1962;Childs, 1969;Raats and Gardner, 1974;Kessler and Rubin, 1987); however, several recent studies have demonstrated that when hysteresis is accounted for it is possible to obtain significantly improved simulations of observed capillary water flows above a fluctuating water table (i.e. Hinz, 1998;Raubenheimer et al, 1999;Nielsen and Perrochet, 2000;Werner and Lockington, 2003;Cartwright et al, 2005Cartwright et al, , 2009. Our understanding of the influence of this phenomenon on beach surface moisture dynamics remains incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Nielsen and Perrochet () and Cartwright et al . () experimentally and numerically investigated the interaction of water table and capillary fringes, while considering the hysteresis implicitly. Cavazza et al .…”
Section: Introductionmentioning
confidence: 99%